Differences in anthropometric characteristics among junior soccer and volleyball players - Masanovic, B.; Bjelica, D.; Corluka, M. (Journal of Anthropology of Sport and Physical Education, 2019)
The aim of this study was to obtain the relevant knowledge about significant differences in some anthropometric characteristics of junior soccer and volleyball players. The sample included 39 male subjects divided into two subsamples, 25 soccer players and 14 volleyball players. The variables sample included 20 anthropometric measures that defi ned longitudinal and transversal dimensionality of skeleton, volume and mass of the body, and subcutaneous adipose tissue. The results were analysed in a statistical procedure marked as a signifi cance testing of two arithmetic means of the independent samples, a t-test at the level of signifi cance of p<0.05. It was concluded, based on these results, that significant differences occur in body height, body weight, elbow diameter, wrist diameter, ankle joint diameter, lower arm circumference (max), lower leg circumference (max) and abdomen skinfold, while the signifi cant diff erence does not occur in knee diameter, upper arm circumference (min), upper arm circumference (max), lower arm circumference (min), upper leg circumference (min), upper leg circumference (max), lower leg circumference (min), upper arm skinfolf, lower arm skinfold, thigh skinfold, calf skinfold and chest skinfold. Therefore, these findings may give coaches from the region better working knowledge and suggest them to follow recent selection process methods and to be more careful during the process of talent identification.